Psychologie der Vermissung am Beispiel der Kinder von vermissten deutschen Soldaten des Zweiten Weltkriegs - Orlowski, Henning V.; Klauer, Thomas; Freyberger, Harald J.; Seidler, Günter H.; Kuwert, Philipp (Zeitschrift für psychosomatische Medizin und Psychotherapie, 2013)
The psychology of being unaccounted for, based on the example of children of missing German soldiers fromWorld War II Objectives: Despite today's extensive research on the psychosocial consequences ofWorldWar II, the group of wives and children whose husbands or fathers went "missing in action" during the Second World War, has yet to be studied systematically in Germany. The present review article shows the special role the wives, and in particular the children, of missing German soldiers played in society and discusses the impact of their loved ones being unaccounted has had on the mental health of this group. Methods: An overview of current research on the psychosocial status of the war generation is given following a short historical introduction to the theme. Subsequently,we discuss the legal and social situation of the families of missing German soldiers during the postwar decades. Finally, two psychological concepts drawn from the US research show that specific disorders, such as complicated grief or "boundary ambiguity," can occur in the relatives of missing persons and blur the line between hope and grief occurring as a result of ambiguous loss. Results and Conclusion: The psychosocial impact of having a relative go missing has hardly been noticed in the German research tradition after World War II. Particularly in light of the age structure of those directly affected and the experiences of transgenerational transmission this neglected psychosocial research subject urgently needs further scientific investigation, inasmuch as the age of the family members still allows it.